PENGEMBANGAN MODEL EKONOMI SYARIAH BERDASARKAN SURAH AL-BAQARAH AYAT 275-280 - Nazwa Akhiela Salsabila Batubara; Oktavia Ramadhani; Tri Purnama Sari; Sanjai Kurniawan Lubis; Ferizal (CV. BAROKAH PUBLISHER, 2026)
This research discusses the development of sharia economic methods by referring to Surah Al-Baqarah verses 275-280. These verses are the main guidelines in building an economic system based on justice, sustainability, and common good. The main focus is the prohibition of usury, the recommendation to transact fairly, and the importance of sharing in the form of alms or zakat. This research also analyzes the principles of sharia economics and their implementation in modern life to answer global challenges. With a qualitative approach based on interpretation and literature review, this study aims to provide a new perspective on the application of sharia values in the global economic system.